Karakterisasi Struktur Kumarin pada Akar Tumbuhan Langsat (Lansium domesticum Corr.) - Nurapita, Riska; Rudiyansyah; Harlia (Jurnal Riset Kimia, 2024)
Lansium plants produce not only terpenoids as the main constituent but also contain phenolics on the basis of phytochemical analysis. Unfortunately, there are still limited information about phenolic structures from this plants. This study was conducted to identify one of phenolic structures from chloroform fraction of Lansium domesticum root. The chloroform fraction was fractionated and purified by chromatographic techniques such as vacuum liquid chromatography (VLC) and column chromatography (CC) to obtain a coumarin. Additionally, the coumarin structure was characterized by 1H-NMR. The isolated coumarin showed a positive result for the phenolic test with FeCl3 5%. The 1H-NMR spectrum of isolated coumarin revealed chemical shifts at δH 7,60 (1H, d, J = 9,5 Hz), 6,92 (1H, s), 6,84 (1H, s), 6,27 (1H, d, J = 9,5 Hz), 6,14 (1H, s), and 3,95 (3H, s). Based on those results and comparison with literature data, it can be concluded that the isolated coumarin is iso-scopoletin (1)